RIDGE-MM SEBAGAI SALAH SATU METODE REGRESI RIDGE YANG ROBUST TERHADAP DATA PENCILAN - Sudartianto Sudartianto; Nono Suwarno; Ahmad Taofik (JURNAL ISTEK, 2017)
In regression analysis, least squares method used adjuster, which is used to estimate the regression parameters, contains a lot of weaknesses, if there is data in the multikolinieritas especially coupled with the outliers. To overcome these weaknesses ridge-MMregression method is used. Ridge-MM regression method is a modification of the ridge regression method is based on the MM-estimator.